STUDY OF ADJUVANT PROPERTIES OF CELL-PENETRATING CATIONIC DENDRIMERIC PEPTIDES - Artem Andreevich Shatilov; Anastasiia Vitalevna Shatilova; Aizirek Anarbekovna Asanbaeva; Marina Olegovna Babikhina; Nikolai Georgievich Cherchenko; Oleg Vladimirovich Mislavskii; Sergei Mikhailovich Andreev; Valerii Valerievich Smirnov; Musa Rakhimovich Khaitov (Медицинская иммунология, 2019)
AbstractAdjuvants represent important components of vaccines, including medications for specific immunotherapy, which improve their efficacy and safety. Current scope of vaccines development includes approaches based on adjuvant inclusion into the immunogenic molecule. Such covalent adjuvants vary greatly in chemical structure, and particularly are found among peptides. Peptides have distinct advantages over substances of other chemical classes, such as high efficiency and biodegradation, while dendrimeric cationic peptides are often capable of enhanced transport ability when compared to linear peptides. In this work, the ability to enhance IgG induction was studied for two cationic dendrimeric cell-penetrating peptides with previously reported transmembrane activity: LTP and SA-40. The peptides were obtained by solid-phase synthesis and characterized by mass-spectrometry and zone capillary electrophoresis. To study adjuvant activity, peptides were conjugated with the recombinant protein Bet v 1, a major birch pollen allergen, produced biotechnologically using e. coli. Conjugation was carried out with Michael reaction after modification of the protein with maleimide function. Conjugates were purified by gel chromatography and dialysis, conjugation efficiency was estimated with SDS-PAGE. Conjugates and pure rBet v 1 were used to immunize BALB/c mice to compare IgG levels to rBet v 1 after four injections without using other adjuvants. Mouse blood sera were studied with ELISA for IgG levels against rBet v 1, which was target criteria of the study, as well as against the conjugates and free LTP and SA-40. It was found that both conjugates significantly increased the IgG level to the base protein, while one of them, LTP-rBet v 1, also induced serum reactivity both to itself and to free LTP. The increase in IgG level to rBet v 1 was approximately fourfold in the case of LTP-rBet v 1, and threefold in the case of SA-40-rBet v 1. Based on the results of the study, it was concluded that both LTP and SA-40 possess adjuvant activity. We believe that LTP and SA-40 structures can be used as references in the development of new peptide adjuvants, and SA-40 itself can be used as a covalent adjuvant. In turn, LTP may be seen perspective as a non-covalent adjuvant.